2000
DOI: 10.1177/001088040004100220
|View full text |Cite
|
Sign up to set email alerts
|

Competencies Required for Club Managers

Abstract: A survey of 114 managers of private clubs developed ranked lists of competencies that the managers considered to be important and those they used most frequently. The survey comprised 127 competencies. To get an indication of which competencies are at once important and frequently used, the researchers weighted those two factors to get a consolidated list of competencies that are both important and frequently used. Topping the list were competencies in accounting and finance, F&B management, and human and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 0 publications
5
47
0
Order By: Relevance
“…Consistent with past findings, respondents attribute management success to such intrinsic attributes as having internal locus of control (Brownell, 1994), as well as pursuing self-development, long-term career goals (Ludkin and Juwaheer, 2000) and willingness to make personal sacrifices (Brownell, 1994). Also dating back in the hospitality literature as early as 1988, personal merits and abilities such as possessing professional appearance and poise, practicing good work ethics and having good communication skills have been well established and documented as important management requisites (Tas, 1988;Okeiyi et al, 1994;Tas et al, 1996;Kay and Russette, 2000;Perdue et al, 2000). The importance ratings of these attributes by respondents in this study are consistent with past findings.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with past findings, respondents attribute management success to such intrinsic attributes as having internal locus of control (Brownell, 1994), as well as pursuing self-development, long-term career goals (Ludkin and Juwaheer, 2000) and willingness to make personal sacrifices (Brownell, 1994). Also dating back in the hospitality literature as early as 1988, personal merits and abilities such as possessing professional appearance and poise, practicing good work ethics and having good communication skills have been well established and documented as important management requisites (Tas, 1988;Okeiyi et al, 1994;Tas et al, 1996;Kay and Russette, 2000;Perdue et al, 2000). The importance ratings of these attributes by respondents in this study are consistent with past findings.…”
Section: Discussionsupporting
confidence: 67%
“…Knutson et al (2002) contend that the level of importance placed on any one-success attribute is likely to change over time. Furthermore, current research into requisites for many different hospitality job titles has reported the need for increased knowledge in new core competencies (Woods et al, 1998;Perdue et al, 2000;Chung, 2000;Kay and Moncarz, 2004). Thus, as lodging managers are being confronted with increasingly changing, dynamic work environments over time, continual scholarly study into lodging management requisites for hospitality management success is important and represents a valuable resource to professionals and the lodging industry, overall, and therefore, important for ongoing scholarly study.…”
Section: Introductionmentioning
confidence: 99%
“…That is, there is potential bias in published literature because it tends to focus on studies with high response rate or significant relationships (De Long and Lang, 1992). Lucas (1999) identified that the most important factor contributing to the generally lower response rate to surveys in the hospitality industry is the fragmented Atkinson and Brown (2001) Performance measure Various size hotels 20% (23) Johnson (1999) Management contract Large hotels 20% (50) Lee and Chon (2000) Training practices Various size restaurants 20% (61) Formica and McCleary (2000) Management skills Large hotels 24% (98) Brown and Dev (1999) Performance measure Large hotels 25% (420) Jenkins (2001) Finance Large hotels 26% (35) Perdue et al (2000) Management skills Leisure clubs 29% (128) Buultjens and Howard (2001) Employment relations Registered clubs 32% (435) Gray et al (2000) Marketing Hospitality industry 33% (329) Beck and La Lopa (2001) Career paths Large hotels 36% (447) Feng and Pearson (1999) Selection criteria and skills Large hotels 42% (133) Wilson et al (2000) Skills-contract catering Catering establishments 42% (56) Ghiselli and Ismail (1999) Organisation behaviour Food services industry 43% (196) Mutch (2001) Career paths Pubs of all sizes 43% (99) Harris and Mongiello (2001) Key performance indicators Large hotels 44% (175) Davidson et al (2001) Organisational behaviour Large hotels 44% (616) Lubetkin (1999) Marketing Bed and breakfast 47% (92) Harris and Bonn (2000) Training Foodservice industry 50% (149) Crotts et al (2001) Organisational behaviour Restaurants 53% (79) Li and Leung (2001) Profile and career of female managers Medium/Large hotel 55% (82) Nield and Kozak (1999) Quality Certification Large hospitality enterprises 69% (34) Karamustafa (2000) Marketing Various size hotels (convenient sampling)…”
Section: Potential Response Ratesmentioning
confidence: 99%
“…Barrows and Walsh (2002), for example, observed that the lack of knowledge of the private club industry, in general, was also reflective of the lack of research publications addressing current issues in the private club industry. Perdue et al (2000Perdue et al ( , 2001Perdue et al ( , 2002 were the first group of researchers who identified important competencies applied to private club managers. While they helped identify important competencies required for successful private club managers, these previous studies failed to address some of the most important managerial knowledge, skills, and abilities necessary for effective club management.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sandwith's (1993) competency domain model examined conceptual-creative, interpersonal, leadership, administrative and technical skills. Previous studies of club managers' competencies by Perdue et al (2000Perdue et al ( , 2001Perdue et al ( , 2002 have examined the importance of administrative and technical competencies, but have neglected the importance of leadership, interpersonal, and conceptual-creativity skills. These skills have been identified in other professions as some of the most important skills by organizational leaders (Oss, 2003).…”
Section: Introductionmentioning
confidence: 99%